Phosphate and Thiophosphate Biphenyl Analogs as Steroid Sulfatase Inhibitors. Issue 2 (3rd April 2015) - Demkowicz, Sebastian; Kozak, Witold; Daśko, Mateusz; Masłyk, Maciej; Kubiński, Konrad; Rachon, Janusz
ABSTRACT <table-wrap position="anchor" orientation="portrait"> Preclinical Research </table-wrap> In the present work, we report convenient methods for the synthesis and biological evaluation of phosphate and thiophosphate biphenyl derivatives exhibiting steroid sulfatase (STS) activity. The described synthesis is based on straightforward preparation of biphenyl‐4‐ol and 4′‐hydroxy‐biphenyl‐4‐carboxylic acid ethyl ester modified with various phosphate or thiophosphate moieties. The inhibitory effects of these compounds were tested on STS isolated from human placenta and led to two compounds of interest, 5a and 5d with IC50 values of 28.0 and 22.1 µM, respectively and that had interesting new binding modes in the STS active site. Drug Dev Res 76 : 8294–104, 2015. © 2015 Wiley Periodicals, Inc.